DNAJC12 as a Mediator Between ESR1 and ERBB4 in Breast Carcinoma Cells - Lin, Mianjie; Wang, Ya-Nan; Ye, Yixin; Xiong, Zhelei; Guo, Fengbiao; Chen, Haibin (Frontiers in Oncology, 2021)
Mutation of the DNAJC12 gene is typically associated with non-progressive Parkinsonism, but is also detectable in breast carcinoma where its contribution and mechanisms are unexplored. In breast carcinoma, ESR1 was positively correlated with DNAJC12 and ERBB4, and DNAJC12 was positively correlated with ERBB4. We used the GEO2R tool to compare differential gene expression of MCF-7 cells, following ESR1 knockdown (GEO database, E-GEOD-27473 array), and found decreased expression of DNAJC12 and ERBB4 in ESR1-silenced MCF-7 cells. The number of identical genes having correlativity with ESR1, DNAJC12, or ERBB4 was 12,165 (66.41%). These results suggest that ESR1 can promote the expression of DNAJC12 and ERBB4, and DNAJC12 can enhance the expression of ERBB4 in MCF-7 cells, implying that there may be a regulatory network among these three genes.